Environmental conditions promote local segregation, but functional distinctiveness allows aggregation of catfishes in the Amazonian estuary. (5th April 2021) - Soares, Bruno E.; Benone, Naraiana L.; Barthem, Ronaldo B.; Marceniuk, Alexandre P.; Montag, Luciano F.A.
Abstract: Co-occurrence patterns of species can appear through niche-related processes such as (i) environmental filtering matching specific sets of traits to a given environment, and (ii) limiting similarity selecting divergent functional traits to reduce niche overlap. Locally, both processes should act together to shape the distribution of species. We evaluated the importance of environmental variables and functional distinctiveness to the co-occurrence patterns of nine marine catfishes in the inner estuary of the Amazon River mouth. Sampling was carried out in the dry seasons of 1996 and 1997, and the rainy season of 1996 by nearly 120 standardized bottom trawls per expedition. We observed 13 significant pairs of segregated species and two pairs of aggregated species, which sum 41.7% of all combinations. Amphiarius phrygiatus and Sciades couma segregated from all the remaining marine catfishes by occupying shallower areas with lower salinity levels. Aggregated pairs were strongly associated with higher functional distinctiveness. We concluded that environmental filtering is the main force structuring the co-occurrence patterns by promoting spatial segregation, but functional distinctiveness allowed some species to aggregate. Highlights: The cooccurrence of species is shaped by environmental filtering and limiting similarity. We studied the cooccurrence of marine catfishes in the Amazon River estuary. Marine catfishes exhibited a high rate of non-random cooccurrence structure. Non-random pairs were mostly segregated due to differences in salinity and depth. Aggregated pairs promoted high functional distinctiveness.